An In-Depth Analysis of the Altman’s Failure Prediction Model on Corporate Financial Distress in Uchumi Supermarket in Kenya - Shisia, Adam; Sang, William; Waitindi, Serah; Okibo, Walter Bichanga (European Journal of Business and Management, 2014)
Many firms in developing and transitional economies are in financial distress situation, due to low level of debt service coverage. The study of financial distress has become a significant global issue after the global financial crisis of 2008. The soaring global financial crisis which has resulted to increased cases of business failures resulting from the effect of bankruptcy as well as insolvency. This study therefore was conducted with the objective of Altman’s failure prediction model in predicting corporate financial distress in Uchumi Supermarkets in Kenya. The study sourced data from secondary sources. The data was obtained from financial reports, library, and organization’s records such as in-house magazines, journals, publications as well as website and other resourceful information available at the Uchumi supermarket secretariat for 5 years from 2001 to 2006. The data extracted include ratios such as current assets and liabilities, total assets, retained earnings, earnings before interest and taxes, book value of the equity and sales. Data analysis involved preparation of the collected data, coding, editing and cleaning of data in readiness for processing using SPSS and Microsoft office excel. In the analysis, Multivariate Discriminant Analysis (MDA) statistical technique as used by Altman (2006) was adopted. Altman (2006) is of the opinion that ratios measuring profitability, liquidity and solvency are the most significant ratios. The study has established that the Altman failure prediction model was appropriate to Uchumi supermarket as it recorded declining Z-score values indicating the company experienced financial distress and that is why the company was delisted from the NSE in 2006. In line with these results, the study has recommended that; the policy makers of Uchumi supermarket should continuously adopt the use of Altman failure prediction model in order to determine the growing of the company and the state in which the company occurs as recommended by the Altman model in which there are safe zone, grey zone and distress zone. This study highly recommends to the potential investors in companies to use the Altman failure prediction model as an assessment tool. The results could raise certain questions about the state of a company and could ultimately result in an investor investing or purchasing a company that is profitable and well-managed company since declining Z-score values depicts a failing company
Keywords: Financial Distress; Financial Ratio; Altman’s Failure Prediction Model